A self-management package for pulmonary fibrosis: A feasibility study - Joanna Y.T. Lee; Gabriella Tikellis; Mariana Hoffman; Christie R. Mellerick; Karen Symons; Janet Bondarenko; Yet H. Khor; Ian Glaspole; Anne E. Holland (PEC Innovation)
Background and objective: There is currently no self-management package designed to meet the needs of people with pulmonary fibrosis (PF). This study evaluated the feasibility and acceptability of a PF-specific self-management package. Methods: Adults with PF were randomly allocated (1:1) to either receive the self-management package with healthcare professional (HCP) support or standardised PF information. Primary outcomes were feasibility and acceptability of the intervention. Secondary outcomes included health-related quality of life, self-efficacy, breathlessness, daily steps, use of PF-related treatments, and healthcare utilisation. Participants' experiences of using the package were explored using qualitative interviews. Results: Thirty participants were included. Recruitment rate was 91% and 100% of those recruited were randomised. Eighty-seven percent of participants who received the package read ≥1 module and set a goal. Secondary outcomes were feasible to collect with high assessment completion rates (87%). Most participants reported the package was easy to use and enhanced knowledge, but suggested some improvements, while HCP support was highly valued. Conclusion: A PF-specific self-management package was feasible to deliver and requires further testing in a trial powered to detect changes in clinical outcomes. Innovation: This is the first self-management package designed specifically for people with PF, informed by patient experience and expert consensus.